Eragrostis pilosa (L.) P. Beauv. (Poaceae) in Poland - Nobis, Marcin; Nobis, Agnieszka (Biodiversity: Research and Conservation, 2010)
The paper presents new data on the occurrence of Eragrostis pilosa in Poland. The species has been considered as an ephemerophyte in the Polish flora. A new locality of E. pilosa was found in the railway areas of Nowosielce near Sanok (southern Poland) in 2007. The occurrence of the species at this locality was confirmed in 2008 and 2009. Because the species is established in anthropogenic habitats, it might be regarded as an epecophyte in Poland.